Pengaruh Profitabilitas(ROA), Leverage, Borad Size, Gender Diversity, Dan Struktur Kepemilikan Terhadap Integrated Reporting - Soegiarto, Dwi; Novianti, Yeni; Delima, Zamrud Mirah (Jurnal Keuangan dan Bisnis, 2022)
Integrated Reporting is a concise communication about the company's strategy, governance, prospects, performance that leads to the external environment in order to create short, medium and long term value. This study aims to determine the effect of profitability (ROA), Leverage, Board Size, Gender Diversity, and Ownership Structure on Integrated Reporting. The data tested is secondary data. This type of research is quantitative with multiple linear regression data analysis techniques using the SPSS 25 application. The population of this study are companies engaged in banking services listed on the IDX for the period 2017-2020. Purposive sampling method was used to produce a sample of 63 samples. The results of this study indicate that leverage has a positive effect on integrated reporting while profitability (ROA), size of the board of directors, gender diversity and ownership structure have no effect on integrated reporting.